Toxic effects of Rhodamine B on antioxidant system and photosynthesis of Hydrilla verticillata - Sharma, Jyotshana; Sharma, Shubhangani; Bhatt, Upma; Soni, Vineet (Journal of hazardous materials letters, 2022)
Rhodamine B is a synthetic dye released in huge quantities as hazardous colored effluents into aquatic ecosystems. It negatively affects the metabolic and physiological processes in aquatic plants. The goal of current study was to assess the impact of various Rhodamine B concentrations (5, 10, 15, 20, and 25 mg/L) on antioxidant and photosynthetic performance of Hydrilla verticillata exposed for 24, 48, and 72 h. Results of present study clearly demonstrate that Rhodamine B inhibits the activity of the superoxide dismutase (SOD), catalase (CAT), and guaiacol peroxidase (GPOD) in H. verticillata. Activities of SOD, CAT, and GPOD were constantly raised at lower concentrations and then decreased with increasing concentration and exposure duration of Rhodamine B. In vivo chlorophyll fluorescence experiments were used to examine its inhibitory effects on H. verticillata photosystem II (PSII). The OJIP fluorescence induction kinetics were altered by increasing the Rhodamine B concentration and treatment time as a result increasing the parameters Fo/Fm and φDo while decreasing Fm, φPo, Ψo, φEo, RC/CSm, ABS/CSm, TR/CSm, ET/CSm and, PIabs. When exposed to Rhodamine B, electron transport is slowed down on both the acceptor and donor sides and overall decreases the photosynthetic performance of H. verticillata. [Display omitted] •Rhodamine B is a hazardous colored effluent that negatively affects aquatic plants.•Antioxidant activity and chlorophyll a fluorescence of H. verticillata was affected by Rhodamine B concentrations (5–25 mg/L).•Rhodamine B reduced PS II donor site and the acceptor side, resulting in PSII RC were damaged.